RPG como caminho: uma proposta de material didático digital para ensino de variação linguística regional - Araujo, Elizete Rodrigues de (2023)
Studies point out that RPG (Role-Playing Game) has become an efficient teaching tool in the most diverse areas, mainly because it involves two elements so valued by young people, the fascination with the ludicity of games and student protagonism, since they are the students responsible for developing their own interactive narratives. For this reason, we chose this hypergenre for teaching linguistic variation, more specifically regional variation, in the semantic-lexical aspect of the language, considering the need to address issues that often cause stigma and prejudice to students from certain Brazilian regions. , when moving to another region. This is an action-research with a qualitative and quantitative approach. The motivation for this work arose from the need we felt to offer the teacher more attractive and interactive classes for teaching content, so that they are not just focused on traditional grammar, but are focused on the plurality of discourses, as preached by the National Base Common Curricular (BNCC), guiding document of Brazilian education, which assumes the enunciative-discursive perspective of language. Furthermore, the present study is also justified by the importance given to multiliteracies and the use of Digital Information and Communication Technologies (TDIC) in that same document, which demonstrates the alignment of the research with the connected and interactive world in which we live. Thus, this research aims to develop a proposal for Digital Didactic Material (MDD) for teaching regional linguistic variation with a semantic-lexical aspect through RPG. For this, we sought theoretical basis in research on three axes: (i) linguistic variation, from the perspectives of Dialectology, Geolinguistics and Sociogeolinguistics, and also the importance of the lexicon in regional variation; (ii) the RPG and its game and hypergenre characteristics, as well as its relationship with the genres of narrative sequences, prioritizing cordel literature, the focus of this study, also including literary literacy; (iii) the pedagogy of multiliteracies and the construction of digital didactic material. Thus, we are guided by studies by Bagno (2007); Sewed (1979; 1982); Christianini (2007); Encarnação (2010); Faraco (2008); Santos (2010); Huizinga (2019 [1938]); Ricon (2002); Bonini (2011); Morales (2019); Cavalcanti (2007); Cosson (2006); Dudeney, Hockly and Pegrum (2016); Red (2017); Rojo and Moura (2012); among others. The data collected showed that RPG brings important contributions to work with variation in the semantic-lexical aspect, in addition to contributing to the minimization of linguistic prejudice. The product of this study resulted in a navigable teaching prototype, in student and teacher versions, with the availability of the material used in the workshops.